DIVERSITAS MANAJEMEN DAN DIVERSIFIKASI PENDAPATAN SEBAGAI FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERBANKAN (Studi Empiris Pada Perbankan yang Terdaftar di BEI Periode 2010 – 2014) - Sayydatuz Shoimah Jamruddin; Nova Novita (Jurnal Akuntansi, 2017)
Ideally, there is no difference perception between members of an organization toward internal auditor roles. This study identified the perception between employees and lecturers of University of Bengkulu; whether the internal auditor as audit snoop, consultant, or Management representative. Data is analyzed using independent sample t test. The research results show that there are difference perceptions between employee and lecturers toward the role of internal auditor as audit snoop and as a consultant. However, this study found no difference perceptions among them on the role of internal auditor as management’s representative. Major role of internal auditor according to employee and lecturers at the University of Bengkulu is the role of as a consultant.Keywords : Internal Auditor, Role, Audit Snoop, Consultant, Management’s Representative